A computational study on the drag reduction effectiveness of a spinning projectile with different afterbody configurations at supersonic speeds - Nguyen, Tuan (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: In this paper, five Army-Navy Spinner Rocket configurations with different afterbodies were numerically evaluated on drag reduction effectiveness at supersonic speeds. Methods: Reynolds-Averaged Navier-Stokes equations with SST k-ω turbulence model were employed for numerical simulations. Mesh sensitivity studies were undertaken to ensure the independence of simulation results on mesh size. Simulation results were validated against archival experimental data. Comparison of aerodynamic drag coefficients for baseline and modified afterbodies was carried out. The flow fields around different afterbody configurations were visualized and analyzed. Results: The research results have indicated that a conical boattail or a combination of a conical boattail with a base cavity are the most effective methods showing on the average 10.99% and 11.96% in drag reduction respectively. The base cavity configuration alone is the least effective method showing an average drag reduction of only 1.33% compared to the baseline configuration. The multi-step afterbody configuration can come up with an average drag reduction of 2.15% compared to the baseline configuration. Conclusion: Afterbody configurations significantly affect the aerodynamic drag of a spinning projectile. Of the considered afterbody configurations, the combination of conical boattail and base cavity is the most effective way to reduce a projectile drag. The findings presented in this study have provided significant insights to better understanding the passive methods for aerodynamic drag reduction.